2017
DOI: 10.1177/2156759x18773599
|View full text |Cite
|
Sign up to set email alerts
|

Promoting STEM Career Development Among Students and Parents of Color

Abstract: To date, millions of dollars have been spent in hopes of bolstering an increase among students of color pursuing science, technology, engineering, and math (STEM) professions. School counselors are uniquely positioned to contribute to this increase; however, they often miss the significance of their leadership role in improving STEM opportunities, particularly for students of color. The results from this qualitative study point to systemic variables that hinder such engagements and provide implications for sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In a qualitative study of the promotion of STEM career development, school counselors stated that their graduate programs included training on career development, but that they had received little to no STEM-related career education either in those programs or by their school districts (Shillingford et al, 2017). Shillingford et al (2017) shared that these counselors reported acquiring basic knowledge of STEM professions and necessary requirements and skills mainly from their own self-directed searches. These efforts to increase their knowledge of STEM professions suggest a realization of the importance of making students aware of STEM-related careers and recommended prerequisites.…”
Section: School Counselor Characteristicsmentioning
confidence: 99%
“…In a qualitative study of the promotion of STEM career development, school counselors stated that their graduate programs included training on career development, but that they had received little to no STEM-related career education either in those programs or by their school districts (Shillingford et al, 2017). Shillingford et al (2017) shared that these counselors reported acquiring basic knowledge of STEM professions and necessary requirements and skills mainly from their own self-directed searches. These efforts to increase their knowledge of STEM professions suggest a realization of the importance of making students aware of STEM-related careers and recommended prerequisites.…”
Section: School Counselor Characteristicsmentioning
confidence: 99%
“…In terms of our reflexivity, the coding team (first and second author) discussed our positions as white women in different positions of power (professor, student), and the experience one of us had as a prior STEM major, and that neither of us was an under-represented ethnic minority, which may limit what we observed (see Levitt, Bamberg, Creswell, Frost, Josselson, & Suárez-Orozco, 2018). We immersed ourselves in the literature on URMs in STEM, including qualitative papers that privilege the voices of participants and papers by scholars of color (e.g., Nasir & Shah, 2011;Shillingford, Oh, & Finnell, 2017;Syed et al, 2011;Winston, Wall Rice, Bradshaw, Lloyd, Harris, Burford, ... & Burrell, 2004).…”
Section: Analytic Proceduresmentioning
confidence: 98%
“…The low rates of higher education attainment for students with LIEM raise concerns about whether the students who wish to pursue higher education have access to courses that support their readiness for college (U.S. Government Accountability Office [GAO], 2018). Unfortunately, a plethora of research has demonstrated a lack of support and even gatekeeping of underrepresented students from participating in rigorous academic programs and testing, such as the SAT test, Advanced Placement (AP) courses, and International Baccalaureate programs (Education Trust, 2022;Hirschi & Smith, 2023;Shillingford et al, 2018;Wanzo, 2014). Moreover, AP programming still mimics earlier patterns of curricular segregation within schools (Hirschi & Smith, 2023;Kolluri 2018;Malkus, 2016;Price, 2021), with students with LIEM being four times less likely to take AP courses compared to their non-economically marginalized peers (Chatterji et al, 2021;Siegel-Hawley et al, 2021).…”
Section: The Role Of High School Counselors: College and Career Readi...mentioning
confidence: 99%
“…Research on students with LIEM and the influence of high school counselors on their pathways to engineering is sparse (Brookover, 2021; Cabell et al, 2021). However, access to high school counseling services can play a critical role in determining which students pursue postsecondary engineering pathways (Brookover, 2021; Nikischer et al, 2016; Shillingford et al, 2018). School counselors’ belief about students with LIEM is one factor that can lead to differences in encouragement toward engineering (Oleka & Mitchell, 2022) and rigorous preparatory courses (Brookover, 2021).…”
Section: The Role Of High School Counselors: College and Career Readi...mentioning
confidence: 99%
See 1 more Smart Citation